Albert & the whale - Hoare, Philip 1958- (4th Estate, 2022)
"In Albert & the Whale, Philip Hoare sets out to discover why Dürer's art endures. He encounters medieval alchemists and modernist poets, eccentric emperors and queer soul rebels. He witnesses the miraculous birth of Dürer's fantastical rhinoceros, and he traces the fate of the star-crossed leviathan that the artist pursued. And as the author swims from Europe to America and beyond, these prophetic artists and downed angels provoke awkward questions. What is natural or unnatural? Is art a fatal contract? Or does it in fact have the power to save us?"--Cover page 4
Originally published: 2021
Keywords: Dürer, Albrecht -- 1471-1528; Dürer, Albrecht / 1471-1528 / Criticism and interpretation; Dürer, Albrecht / 1471-1528; Criticism, interpretation, etc